A Postcard to an Anonymous Reader: Lima Barreto’s Brazilian Diction in the Magazine Careta - Correa, Felipe Botelho (Brasiliana: Journal for Brazilian Studies, 2013)
This article analyses Lima Barreto’s Brazilian diction as suggested by Manuel Bandeira in 1929. I focus on the period between 1915 and 1922 when Lima Barreto collaborated to the magazine Careta, one of the most popular publications in that period, circulating widely within Brazil and abroad. I argue that Lima Barreto’s Brazilian diction goes beyond grammar and collocation issues and can be regarded as connected to the emerging visual culture of the period. In Careta he was able to reach a nationwide audience in a context of great advance of images over belletrism. In this context, I point out that Lima Barreto did not react against this process and indeed incorporated pictorial strategies into his pieces of mass circulation.